The effects of elevated CO2 on the growth and toxicity of field populations and cultures of the saxitoxin‐producing dinoflagellate, Alexandrium fundyense. (31st December 2014) - Hattenrath‐Lehmann, Theresa K.; Smith, Juliette L.; Wallace, Ryan B.; Merlo, Lucas R.; Koch, Florian; Mittelsdorf, Heidi; Goleski, Jennifer A.; Anderson, Donald M.; Gobler, Christopher J.
Abstract The effects of coastal acidification on the growth and toxicity of the saxitoxin‐producing dinoflagellate Alexandrium fundyense were examined in culture and ecosystem studies. In culture experiments, Alexandrium strains isolated from Northport Bay, New York, and the Bay of Fundy, Canada, grew significantly faster (16–190%; p < 0.05) when exposed to elevated levels of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf356w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> (∼ 90–190 Pa = 900–1900 μatm) compared to lower levels (∼ 40 Pa = 400 μatm). Exposure to higher levels of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf35fr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> also resulted in significant increases (71–81%) in total cellular toxicity (fg saxitoxin equivalents cell−1) in the Northport Bay strain, while no changes in toxicity were detected in the Bay of Fundy strain. The positive relationship between <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf35hv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> enrichment and elevated growth was reproducible in natural populations from New York waters. Alexandrium densities were significantly and consistently enhanced when natural populations were incubated at 150 Pa <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf35b3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> compared to ∼ 39 Pa. During natural Alexandrium blooms in Northport Bay, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf35cn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> concentrations increased over the course of a bloom to more than 170 Pa and were highest in regions with the greatest Alexandrium abundances, suggesting Alexandrium may further exacerbate acidification and/or be especially adapted to these acidified conditions. The co‐occurrence of Alexandrium blooms and elevated <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf34p3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> represents a previously unrecognized, compounding environmental threat to coastal ecosystems. The ability of elevated <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3tpf34nj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PCO2</alternatives> to enhance the growth and toxicity of Alexandrium indicates that acidification promoted by eutrophication or climate change can intensify these, and perhaps other, harmful algal blooms.